Strategi Survival Gelandangan di Kota Manado - Tateki Yoga Tursilarini (Jurnal Penelitian Kesejahteraan Sosial, 2013)
The existence of homeless in municipal society is unwanted, they are identical with groupÂ which is difficult to be arrange, has their own value, and having rather negativeÂ attitude. The research is to describe factors they become and several strategies they can survive living in the city. Data resources are gathered from homeless, related institution commiting in homeless such as social agencies (municipality and province), police office, Pelita Kasih Non-government Organization, and Commision for Children Protection. Data are gathered through interview, focus group discussion, observation, and documentary analysis techniques. Data gathered are analyzed through qualitative and quantitative techniques. The factors they become homeless are caused by selves internal conditions, such as physical, visional, and leprousy handicap. The external factors are family conflict, economic presure, educational and skill limited. The homeless hold several strategies, sort of luring compasionate, feeling enough to eat, set their own value and norm, change their place every time, create their own job, snap the chance if it is possible, follow government program, and solidarity among them. It is recommended that social agency and related institutions under local government, as policy makers, should put forward: the homeless social needs based on their own, looking homeless wholy as humankind from physical, psichological, and social aspect to develop municipality as a whole community. For the people around the homeless are expected to give chance and room for the homeless existence.